The Literature of Highway Finance - Breithut, R. C. (Quarterly Journal of Economics, 1939)
Early discussions, 590. — Report of the Conference on Rail and Road Transport, 592. — Comments, 593. — Recommendations of the Joint Committee of Railroads and Highway Users, 594.—The allocation of cost: Sandage and Nelson, 595. — The National Transportation Committee, 597. — Physical vs. economic road life, 598. — Owen's views, 599. — Motor transportation's share of the cost of general government, 600. — Inadequacy of available data, 601. — Surveys now being undertaken in coöperation with the Federal Government, 601. — Dangers in the use of these data: Fairbank's Toll Roads and Free Roads, 605. — Comments, conclusions, 609.